Settlement of Mild Criminal Offence of Livestock Theft Based on Aceh Qanun Number 9 Year 2008 in Aceh - M. Ramadhan S.; Aspan, Henry (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Aceh is a provincial area which is a special legal community unit and is given special authority to regulate and manage its own government affairs and the interests of the local community. Minor crimes that can be resolved by customary institutions as mandated by Article 13 of Aceh Qanun Number 9 of 2008 concerning the Development of Customary Life and Customs that can be resolved in a customary manner through customary institutions. Meurah Mulia District, North Aceh Regency also practices the settlement of minor crimes based on Qanun Number 9 of 2008. The problem to be studied in this study is the Implementation, Settlement of Minor Criminal Acts of Theft of Livestock. The approaches used in this thesis are the Historical approach, the Sociological approach, and the Normative approach. The types of research are field research and library research. The data analysis model uses an interactive model, namely data reduction, data reduction presentation and conclusions. The minor crime of livestock theft that occurred in Meurah Mulia District, North Aceh Regency has been implemented properly according to the regulations in Qanun Number 9 of 2008 with different verdicts. The settlement of the minor crime of livestock theft is carried out using peaceful settlement and compensation. The minor crime of livestock theft that occurred in Meurah Mulia District, North Aceh Regency has ended effectively. The effectiveness indicator is assessed from the completion of the entire series of settlements of the minor crime of livestock theft in accordance with Article 16 of Aceh Qanun Number 9 of 2008.